ESTETIKA HINDU PADA TARI GANDRUNG DALAM UPACARA PIODALAN DI PURA DALEM, BANJAR TAMBAWU KELOD, DESA TAMBAWU, KELURAHAN PENATIH, KECAMATAN DENPASAR TIMUR - I Made Sugiarta; Ni Luh Putu Wiwin Astari; I Gusti Putu Wulan Santika Puspita (UNHI PRESS, 2021)
Hinduism is the main source of the values ​​that animate Balinese culture, therefore every result of cultural creativity, including art, cannot be separated from noble values, especially aesthetic values ​​that come from Hinduism. In the implementation of religious activities, art has always been an important part of the success of the religious ceremonies that are held. In Tambawu village, we never miss to carry out the yadnya ceremony, this is based on the awareness of the community that everything is based on the gift of Ida Sang Hy ang Widhi Wasa. In carrying out the Dewa Yadnya ceremony, it is not only poured out in an offering in the form of Upakara but also presented sacred arts generation. Existence Gandrung dance is one type of sacred dance that is functioned in the bebali art setting during the Piodalan ceremony at Pura Dalem , Tambawu Village, which is presented every six months, on Tilem day after Buda Kliwon Paang . The problems at this writing include; 1) B How can the form of offering dance Infatuated , 2) What Functions dance gandrung , and 3) Is the Hindu aesthetics (tattva, ethics, ritual) in dihadirkannya dance gandrung on Piodalan at Pura Dalem , Tambawu village. The conclusion of its cover; (1) The form consists of dancers dance Infatuated , Range of motion , structure pe rsembahan dance Infatuated , Tata makeup and clothing, Upakara , music accompaniment, and place dihadirkannya . (2) The functions of tri Gandrung are Religious Functions, Social Functions , Hindu Religious Education Functions , and Cultural Preservation Functions. While the values ​​contained in the offerings of the Gandrung dance are the values of tattwa , morality and ceremonies